Responsible Factors for Decline of an Organized Retail Sector: A Case Study of Samabayika in West Bengal - Bhattacharyya, Pinaki Ranjan; Laha, Sourav (Indian Journal of Marketing, 2010)
Indian retail industry is the largest industry in India, with an employment of around 8% and contributing to over 10% of the country’s GDP. Retail industry in India is expected to rise 25% yearly being driven by strong income growth, changing lifestyles, and favorable demographic patterns. (www.business.mapsofindia.com) The network of retailers has reached every nook and corner of the country. So any product produced anywhere in the country can be easily accessed by the buyers from any location. Thus, the spatial convenience of Indian retailers is very high. According to ORG-MARG, the total number of all kind of retail outlets in India was 51,30,000 during 1996-97. This means that one retail outlet exists against an average of almost 190 persons. (Sarma, 2000)